Surgical outcomes are equivalent after pure laparoscopic and robotic-assisted pyeloplasty for ureteropelvic junction obstruction. Issue 6 (December 2020) - Ebert, Kristin M.; Nicassio, Lauren; Alpert, Seth A.; Ching, Christina B.; Dajusta, Daniel G.; Fuchs, Molly E.; McLeod, Daryl J.; Jayanthi, Venkata R.
Summary: Introduction: Minimally invasive (robotic and pure laparoscopic) pyeloplasty has been increasingly used for treatment of ureteropelvic junction obstruction (UPJO). However, few large-scale studies have compared these two modalities directly. Methods: We performed a retrospective single-center review of all patients who underwent pure laparoscopic (LP) or robotic pyeloplasty (RALP) between 2007 and 2018. Patients were excluded if the initial surgery at our institution was a redo pyeloplasty or if they lacked follow-up information. Outcomes of interest included operative time, length of stay, and complication rates, including rates of secondary procedures. We compared these outcomes between groups using Student's t test for continuous variables and a Chi-square for categorical variables. Results: A total of 282 patients were identified. Forty-eight were excluded based on study criteria; therefore, our total study cohort was 234 patients: 119 RALP and 115 LP cases. Overall mean postoperative follow-up time was 20.8 months, with no significant differences between groups. Mean operative time was shorter in the LP group when compared the RALP group (3 h 7 min vs. 3 h 41 min, p < 0.001). There were no significant differences between groups in length of stay (1.22 days vs 1.50 days, p = 0.095). Complications occurred in 52 patients (22.2% of overall cohort) with no difference in incidence between groups. Twenty-five patients (14 in the RALP group and 11 in the LP group) underwent unplanned secondary procedures; 19 of these patients (9 in the RALP group and 10 in the LP group) needed a procedure to address secondary obstruction. Conclusion: We demonstrated no significant differences between RALP and LP in regards to complication rates. Surgeons performing RALP and LP have the potential to offer the same level of care for the surgical management of UPJO, especially in countries where robotic technology may not be readily available. Median time from surgery to complication in days (range) Overall (n = 234) Robotic (n = 119) Laparoscopic (n = 115) p value Clavien I 9 (3–26) 9 (3.8%) 5 (4.2%) 4 (3.5%) p = 1.0 Clavien II 12 (3–37) 17 (7.3%) 8 (6.7%) 9 (7.8%) p = 0.75 Clavien III 33 (4–1316) 25 (10.7%) 14 (11.8%) 11 (9.6%) p = 0.59 All complications 17 (3–1316) 52 (22.2%) 28 (23.5%) 24 (20.9%) p = 0.63